Security Analysis of Scalable Block Cipher PP-1 Applicable to Distributed Sensor Networks. (30th September 2013) - Lee, Yuseop; Jeong, Kitae; Sung, Jaechul; Lee, Changhoon; Hong, Seokhie; Chang, Ku-Young
PP-1 is a scalable block cipher which can be implemented on a platform with limited resource. In this paper, we analyze the security of PP-1 by using truncated differential cryptanalysis. As concrete examples, we consider four versions of PP-1, PP-1/64, PP-1/128, PP-1/192, and PP-1/256. Our attack is applicable to full-round versions of them, respectively. The proposed attacks can recover a secret key of PP-1 with the computational complexity which is faster than the exhaustive search. These are the first known cryptanalytic results on PP-1.